Two‐Stage Enzymatic Hydrolysis for Fermentable Sugars Production from Damaged Wheat Grain Starch with Sequential Process Optimization and Reaction Kinetics - Sirohi, Ranjna; Pandey, Jai Prakash; Goel, Reeta; Singh, Anupama; Lohani, Umesh C.; Kumar, Anil (Die Stärke, 2021)
Damaged wheat grains are usually discarded following which they decompose naturally to cause environmental pollution. The potential conversion of these starchy substrates to usable fermentable sugars is the subject of this study. Wheat grains in different quantities (10–20%, w/v) are liquefied using different concentrations of α‐amylase (1−5% v/v; 12−60 U mL−1) to generate hydrolysate. The process is optimized to obtain the maximum concentration of reducing sugars. The concentration of reducing sugars obtained after 60 min of liquefaction is quantified as 85.2 mg mL−1 using 5% v/v α‐amylase and 19.4% w/v substrate in the hydrolysis media. Reaction kinetics confirm that substrate concentrations higher than 10% w/v can enhance the production of fermentable sugars. The obtained hydrolysate is subjected to saccharification using glucoamylase (1−3% v/v; 46−138 U mL−1) for the conversion of remaining oligosaccharides and α‐limit dextrins to fermentable sugars. Optimum glucoamylase concentration of 2.4% v/v in the reaction media yields 147.5 mg mL−1 fermentable sugars in 103 min. Predictive second‐order models are established for the process with good accuracy. Subsequent experiments at optimum conditions are performed for model validation. Wheat grains are often damaged during pre‐ and post‐harvest operations and are thrown away as waste which attracts pathogenic microorganisms and causes environmental pollution. This work optimizes a biochemical process that efficiently converts damage wheat grains to fermentable sugars that can be used for developing biodegradable plastics and industrial chemicals. The work has potential applications in biochemical/bioprocessing/downstream industries.